The Morphosyntactic and Lexical Data in Serbian Sport Newspapers - Asimopoulos, Panagiotis G. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The intense interest and the dynamic involvement of modern man in sport activities indicates the role of catalytic importance that this social institution reflects at the essential formation and clear expression of similar manifestations. Due to an unimpeded access to this specific nuance of journalistic speech a particular language code has developed. Accordingly despite the caused functional difficulties and linguistic problems established phrases with sentimental background, technical terms and loanwords with international domain incorporated in everyday communication and syntactic irregularities dominate in it. Taking into account the great number of Serbian newspapers that exclusively deal with sports news and the fact that the concerning topic is processed sporadically in spite of the passionate readers of the described events the aim of the paper is to present the basic characteristics related to the morphosyntactic and lexical analysis and also a detailed description of necessary data collected from actual electronic sources.